Identifying SARS-CoV-2 Lineage Mutation Hallmarks and Correlating Them With Clinical Outcomes in Egypt: A Pilot Study - Agwa, Sara H. A.; Elghazaly, Hesham; El Meteini, Mahmoud Shawky; Yahia, Yahia A.; Khaled, Radwa; Abd Elsamee, Aya M.; Darwish, Reham M.; Elsayed, Shaimaa M.; Hafez, Hala; Mahmoud, Basma S.; EM, Fouda; Matboli, Marwa (Frontiers in Molecular Biosciences, 2022)
Background: SARS-CoV-2 pandemic led to over 4.9 million deaths till October 2021. One of the main challenges for creating vaccines, treatment or diagnostic tools for the virus is its mutations and emerging variances. A couple of variances were declared as more virulent and infectious variances from others. Some approaches were used as a nomenclature for SARS-CoV-2 variances and lineages. One of the most used is PANGOLIN nomenclature. Methods: In our study, we enrolled 35 confirmed SARS-CoV-2 patients and sequenced the viral RNA in their samples. We aimed to correlate the clinical outcomes with different viral lineages in Egypt according to PANGOLIN nomenclature. In addition, we wanted to highlight the hallmark mutations in the most frequent lineage. Results: We identified a 7-mutation signature for SARS-CoV-2 C36 lineage, detected in 56 countries and an emerging lineage in Egypt. In addition, we identified one mutation which was highly negatively correlated with the lineage. On the other hand, we found no significant correlation between our clinical outcomes and C36 lineage. Conclusion: C36 lineage is an emerging SARS-CoV-2 that needs more investigation regarding its clinical outcomes compared to other strains. Our study paves the road for easier diagnosis of variances of concern using mutation signatures.